# How does assuming the $\sum_{i=1}^n X_i =0$ change the least squares estimates of the betas of a simple linear regression

First I need to minimize this just like I do with a regular L-S estimates (assuming Gauss-Markov) expect $\sum_{i=1}^n X_i=0$:

$$\sum_i^n e_i^2=\sum_i^n(y_i-\beta_0+\beta_1x_i)^2$$

I take the partial deriviates:

$$-2\sum_i^n(y_i-\beta_0-\beta_1x_i)$$

$$-2\sum_i^n(y_i-\beta_0-\beta_1x_i)x_i$$

Set equal to zero:

$$\sum_i^n y_i-n\beta_0-\beta_1\sum_i^n x_i=0 \rightarrow \sum_i^n y_i-n\beta_0=0 \rightarrow n\beta_0=\sum_i^n y_i \rightarrow \beta_0=\bar{y}$$

$$\sum_i^n x_iy_i-\beta_0x_i-\beta_1x_i^2=0 \rightarrow \beta_1\sum_i^nx_i^2=\sum_i^n x_iy_i \rightarrow \beta_1=\sum_i^n\frac{x_iy_i}{x_i^2}=\sum_i^n\frac{y_i}{x_i}$$

The expected values for these estimates are:

$$E(\beta_0)=E(\bar(y))=E(\frac{\sum_i^n y_i}{n})=\frac{\sum_i^n E(y_i)}{n}=\frac{\sum_i^n \beta_0+\beta_1 \sum_i^nx_i}{n}=\beta_0+0=\beta_0$$

$$var(\beta_0)=var(\bar(y))=var(\frac{\sum_i^n y_i}{n})=\sum_i^n var(\frac{y_i}{n})=\sum_i^n \frac{var(y_i)}{n^2} = \frac{\sigma^2}{n}$$

I think my $\beta_0$ estimates are correct, but I feel like I did something wrong with $\beta_1$

I'd appreciate some guidance

• The last equality for $\beta_1$ does not simplify like that. Be careful with the summation rules. Sep 20, 2015 at 8:39
• Although your question refers to a "change," what is your reference? To what are you comparing these estimates?
– whuber
Sep 20, 2015 at 13:10
• I'm comparing to a regular L-S estimate where you don't assume $\sum_i^n X_i=0$ Sep 20, 2015 at 14:04
• I still don't understand, because to make least-squares fits one knows the values of the $x_i$. Could you explain what it would mean, then, to "assume" the $X_i$ sum to zero? Are you supposing that the $x_i$ are iid draws from some zero-mean distribution?
– whuber
Sep 21, 2015 at 14:35

$$\sum_i^n x_iy_i-\beta_0x_i-\beta_1x_i^2=0 \rightarrow \beta_1x_i^2=\sum_i^n x_iy_i \rightarrow \beta_1=\frac{\sum_i^n x_iy_i}{\sum_i^n x_i^2}$$
$$E(\beta_1)=\frac{\sum_i^n x_iE(y_i)}{\sum_i^n x_i^2}=\frac{\sum_i^n x_i(\beta_0+\beta_1x_i)}{\sum_i^n x_i^2}=\frac{\beta_0\sum_i^n x_i}{\sum_i^n x_i^2}+\frac{\beta_1\sum_i^n x_i^2}{\sum_i^n x_i^2}=\beta_1$$
$$var(\beta_1)=\sum_i^n var(c_iy_i)=\sum c_i^2\sigma^2=\sigma^2 \frac{\sum_i^n x_i^2}{(\sum_i^n x_i^2)^2}=\frac{\sigma^2}{\sum_i^n x_i^2}$$
• Another way of stating the answer to the question in the post is that setting $x^*_i =x_i -\bar{x}$ orthogonalizes the intercept term $\beta_0$ from the remaining coefficients $\beta_i$ for $i=1,2,3 \dots, p$. Jan 12, 2018 at 3:10